2015
DOI: 10.1021/acscatal.5b01114
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Catalysis of Preferential Oxidation of CO in H2-Rich Stream by Gold Single-Atom Catalysts

Abstract: Preferential oxidation of CO (PROX) in H2-rich stream is critical to the production of clean H2 for the H2-based fuel cells, which provide clean and efficient energy conversion. Development of highly active and selective PROX catalysts is highly desirable but proved to be extremely challenging. Here we report that CeO2-supported Au single atoms (Au1/CeO2) are highly active, selective, and extremely stable for PROX at the PEMFC working temperature (∼80 °C) with >99.5% CO conversion over a wide temperature windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
293
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 404 publications
(307 citation statements)
references
References 57 publications
12
293
2
Order By: Relevance
“…The difference of our results from Goodman's work can be attributed to the different morphologies of particles, that is, quasi-spherical particles in our work versus planar (for example, two atomic layer thick) gold particles in Goodman's work42. The calculated turnover frequency of Au 144 is 2 s −1 , which is comparable to the best catalysts reported43. Interestingly, the size trend in the electrocatalytic oxidation of alcohol (Fig.…”
Section: Resultssupporting
confidence: 41%
“…The difference of our results from Goodman's work can be attributed to the different morphologies of particles, that is, quasi-spherical particles in our work versus planar (for example, two atomic layer thick) gold particles in Goodman's work42. The calculated turnover frequency of Au 144 is 2 s −1 , which is comparable to the best catalysts reported43. Interestingly, the size trend in the electrocatalytic oxidation of alcohol (Fig.…”
Section: Resultssupporting
confidence: 41%
“…Among these factors, however, the size of Au NPs might be the most critical: it is generally accepted by now that there is an optimum size range of 0.5-5 nm for CO oxidation. Recent experiments and theoretical calculations, however, have exclusively demonstrated that oxide supported Au single atoms can be extremely active, even better than the small Au clusters and NPs [65,68,69] . As a consequence, the control of the size and size distributions of supported Au NPs and the improvement of their sintering resistance are critical for developing practical supported Au NPs catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Mn-O-C confirms that the active sites of graphene and the dispersed MnO 2 are strongly connected on the surface, thereby confirming the dual-site mechanism. In this mechanism, the two sites must be located sufficiently close to the surface to allow their adsorbed species to easily react with one other [50][51][52].…”
Section: Surface Structure Of the Mno 2 /Graphene Samplementioning
confidence: 99%